The names that have tow plural forms in the Hebrew language (Morphological- Semantical study) - Zena Ayad Qasem , Dr. (lark, 2023)
One of the main topics in the field of morphology is the topic of the plural forms. In Hebrew Language they are made plural by adding a one-syllable suffix to the end of the singular noun. There are two different plural suffixes, one for each grammatical gender, and there are many other Suffixes are used in the Hebrew language to form plurals of nouns and adjectives.This study takes a new form to analyze the plural forms in the Hebrew language, and clarifies the relationship between the morphological form of the name and its meaning, and the plural suffix that it needs.and it tries to discuss the questions, if there is a regular plural forms for all names in the Hebrew language, or if there are unusual names in their plural forms.  This study also tries to clarify all standards that names must have for the plural forms to be regular or irregular.This study highlights specially the names that had two different plural suffixes, and it also interested to shows all the linguistic factors that led to the formation of names with two or more plural forms.And In this study we try to explain the reasons that lead to changing the meaning of same noun with different suffixes, which sometimes it's equal or not equal in his meanings, and sometimes the differences betwen them are historical, or sometimes Because of the commonality, or it may be Semantical.
Keywords: plural, irregular plural, etymological differences, stylistic differences, semantic differences.